2014
DOI: 10.1021/jo502511j
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and Bisquinoline-Annulated Porphyrins from Porphyrin β,β′-Dione Oximes

Abstract: An acid-induced reaction of meso-tetraphenyl-2-hydroxyimino-3-oxoporphyrin leads, with concomitant loss of water, to a formal electrophilic aromatic substitution of the ortho-position of the phenyl group adjacent to the oxime, forming a quinoline moiety. Owing in part to the presence of a π-extended chromophore, the resulting meso-triphenylmonoquinoline-annulated porphyrin (λmax = 750 nm) possesses a much altered optical spectrum from that of the starting oxime (λmax = 667 nm). An oxidative DDQ-induced ring-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 75 publications
1
28
0
Order By: Relevance
“…Furthermore, the extremely nonplanar 18 π‐chromophores of the indachlorins highlight the conformational plasticity of the porphyrinic macrocycle without it losing its key properties of aromaticity and associated high‐extinction UV/Vis spectra. The generally high solubility (in organic solvents) of the indaphyrins also differentiates them from a number of other π‐extended systems 14c. We attribute this apparent lack of stacking to their flexible and nonplanar conformations.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, the extremely nonplanar 18 π‐chromophores of the indachlorins highlight the conformational plasticity of the porphyrinic macrocycle without it losing its key properties of aromaticity and associated high‐extinction UV/Vis spectra. The generally high solubility (in organic solvents) of the indaphyrins also differentiates them from a number of other π‐extended systems 14c. We attribute this apparent lack of stacking to their flexible and nonplanar conformations.…”
Section: Resultsmentioning
confidence: 88%
“…Treatment of the free-base oxime 55 (M = 2H) with p -TSA in toluene at reflux leads to the formation of quinoline-annulated porphyrins [73,74].…”
Section: Chemistrymentioning
confidence: 99%
“…In addition to PPQ itself, a wide range of other bis-4-aminoquinoline compounds have been shown to have antiplasmodial activity, tending to be active against both chloroquine-sensitive (CQS) and CQR strains [17,19,[30][31][32][33][34][35][36][37][38][39][40]. During the 1990s, a study of bis-quinolines by Vennerstrom and co-workers led to the discovery of Ro 48-6910, which was evaluated in preclinical studies but was regrettably found to be phototoxic [19,37,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%